Review on Nested Array Design Research - Mao Yanyuan, Ma Wanyu, Si Weijian (Hangkong bingqi)
Array signal processing is an important branch of signal processing, which is widely used in radar, sonar and wireless communication. Direction of arrival estimation, as one of its key applications, traditionally relies on the layout of uniform linear arrays. However, the estimation performance of such array configuration is quite limited. In recent years, nested arrays have attracted much attention due to their simple structure and significant advantages. The main advantage of nested arrays is that they have the precise expression of sensor positions, and they can achieve a larger array aperture compared to uniform linear arrays in the case of a fixed number of array elements. This feature not only enhances the direction-finding accuracy and resolution, but also opens up new research directions in the field of array design. Aiming at a series of variants of nested array developed in recent years, this paper summarizes the research progress of nested array design methods, analyzes their advantages in array aperture expansion, spatial freedom improvement and mutual coupling reduction, and introduces the application scenarios of nested array design. Finally, it discusses and prospects the development trend of nested array design.